NOISE AND ITS IMPACT ON SOUND PERCEPTION IN URBAN AREAS ADJACENT TO RAILWAY TRACKS - Orynchak, Maria; Mykhaylo , Melnyk (Collection of scientific papers «ΛΌГOΣ», 2023)
Introduction. The rapid urbanization and expanding transportation networks have significantly increased noise pollution in cities, with railway traffic being a prominent contributor to the problem. This study aimed to investigate the impact of railway-induced noise on sound perception in urban areas adjacent to railway tracks. Through comprehensive noise measurements, perception surveys, and soundscape mapping, we sought to understand the complex relationship between railway noise and residents’ auditory experiences.